Transcending national citizenship or taming it ? Ayelet Shachar’s Birthright Lottery - Ivison, Duncan (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2012)
Recent political theory has attempted to unbundle demos and ethnos, and thus citizenship from national identity. There are two possible ways to meet this challenge: by taming the relationship between citizenship and the nation, for example, by defending a form of liberal multicultural nationalism, or by transcending it with a postnational, cosmopolitan conception of citizenship. Both strategies run up against the boundedness of democratic authority. In this paper, I argue that Shachar adresses this issue in an innovative way, but remains ultimately trapped by it. My argument has two parts. In the first one, I look at the analogy between property and citizenship on which Shachar rely to justify the obligations of wealthy states towards the global poor. I suggest that it does not work well to explain the rarity of citizenship and that the idea of taxing its value at the global level, however intuitive in liberal theory on property, could yield unexpected and non-liberal consequences. Nevertheless I also assess its merits. In the second part, I suggest that Shachar’s claim that her argument generates a legal obligation toward the global poor is not binding. It could only be so with the kind of cosmopolitan political institutions that she eschews. Thus we return where we begin.